Mobile Power Allocation Intelligent Optimization Algorithm for Cooperative NOMA Network Based on CBAM-BiLSTM - Xu, Lingwei; Cao, Shubo; Fu, Xingyue; Qin, Xujiang; Li, Xingwang; Gulliver, T. Aaron (IEEE transactions on vehicular technology, 2024)
The non-orthogonal multiple access (NOMA) technology can greatly improve the spectral efficiency of wireless communication systems. The incorporation of NOMA technology into a 5G mobile communication network has the potential to significantly improve communication performance. First, we establish an mobile cooperative NOMA multi-user network. The exact outage probability (OP) expressions are then derived, and the effect of the power allocation on OP performance is investigated. Finally, we design a CBAM-BiLSTM network and propose an intelligent power allocation optimization algorithm based on system efficiency and user fairness. The CBAM-BiLSTM network is a structure based on convolutional block attention mechanism (CBAM) and bidirectional long short term memory network (BiLSTM). CBAM performs feature selection and weights the spatial and channel dimensions of feature maps to improve the network's classification accuracy. BiLSTM can fully utilize contextual information and handle long-term dependencies, thereby providing more comprehensive and accurate modeling capabilities and predictive performance. Simulation results indicate that, compared with the Transformer, ShuffleNetV2, and YOLOv5 algorithms, the CBAM-BiLSTM can obtain more accurate power allocation coefficients and improve system performance. Compared to ShuffleNetV2, CBAM-BiLSTM reduces mean square error (MSE) by 42.8%.